Insights on the Evidence of Cardiotoxicity of Hydroxychloroquine Prior and During COVID‐19 Epidemic - Serena Romani; Alexandre Gérard; Audrey Fresse; Delphine Viard; Élise Van‐Obberghen; Joëlle Micallef; Fanny Rocher; Milou‐Daniel Drici; the French Pharmacovigilance Network (Wiley, 2021)
The recent empirical use of hydroxychloroquine (HCQ) in coronavirus disease 2019 (COVID‐19) revived the interest in its cardiac toxicity, increasingly sidelined over time. We aimed to assess and compare the profile of cardiac adverse drug reactions (CADRs) associated with HCQ before and during COVID‐19. We performed a retrospective comparative observational study using the French Pharmacovigilance network database between 1985 and May 2020 to assess all postmarketing CADRs associated with HCQ notified before COVID‐19 in its approved indications for lupus and rheumatoid arthritis (preCOV), and those concerning its empirical use in COVID‐19 (COV). Eighty‐five CADR in preCOV were compared with 141 CADRs in COV. The most common CADR of preCOV were cardiomyopathies (42.4%) and conduction disorders (28.2%), both statistically more frequent than in COV (P < 0.001). COV notifications significantly highlighted repolarization and ventricular rhythm disorders (78.0%, P < 0.001) as well as sinus bradycardias (14.9%, P = 0.01) as compared with preCOV. Estimated incidence of CADR was significantly higher among patients exposed to off‐label use of HCQ in COVID‐19 (2.9%) than before COVID‐19 in its approved indications (0.01%, P < 0.001). The use of HCQ in COVID‐19 sheds a new light on the spectrum of its cardiac toxicity. This fosters the value of a closer monitoring of all patients treated with HCQ, regardless of its indication, and the importance of an update of its summary of product characteristics.